Peran Mediasi Intellectual Capital Dalam Hubungan Firm Size Dengan Earning Quality - Tangke, Paulus (Jurnal Ilmiah Akuntansi Peradaban, 2023)
This study aims to examine the mediating role of Intellectual Capital in the relationship between Firm Size and Earnings Quality. This study uses the theory of Signal Theory RBV. The population and research sample are manufacturing companies listed on the Indonesia Stock Exchange in 2019 – 2021. This research is an explanatory research that aims to examine the causal relationship between variables. The independent variables in this study are Firm Size and the dependent variable Earnings Quality and Intellectual Capital as mediating variables. The results of this study indicate that firm size has a positive but not significant effect on earnings quality. Firm size has a positive and significant effect on intellectual capital, so does intellectual capital has a positive and significant effect on earnings quality. Intellectual capital can mediate the relationship between firm size and earnings quality